2021
DOI: 10.1080/13102818.2021.1915869
|View full text |Cite
|
Sign up to set email alerts
|

The role of bioactive phytoconstituents-loaded nanoemulsions for skin improvement: a review

Abstract: As the largest organ in the human body, the skin should be protected from various harmful chemicals and pollutants from the surrounding environment and ultraviolet (UVA/UVB) radiation emitted from sunlight. This has prompted formulation scientists to embark on new technology to formulate cosmetics free of synthetic chemicals using natural plant-based extracts as the replacement. Natural phytoanti-oxidants, viz. catechin, quercetin and gallic acid, are polyphenols whose therapeutic values (antioxidative, antity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 143 publications
(155 reference statements)
0
9
0
Order By: Relevance
“…In general, melanogenesis consists of two stages mediated by the tyrosinase enzyme, the first of which is DOPA synthesis and the second of which is DOPA oxidation to dopaquinone. 58 F1 was found to inhibit the tyrosinase activities when the substrates were both L-tyrosine and L-DOPA, with inhibitions of 96.5 ± 0.2% and 87.9 ± 1.4%, respectively. As tyrosinase is an enzyme that plays a part in the metabolic process that generates hyperpigmentation of the human skin via the biosynthesis of melanin in the human skin, the compounds or formulations that possessed anti-tyrosinase activity were appealing for whitening effects.…”
Section: Resultsmentioning
confidence: 96%
“…In general, melanogenesis consists of two stages mediated by the tyrosinase enzyme, the first of which is DOPA synthesis and the second of which is DOPA oxidation to dopaquinone. 58 F1 was found to inhibit the tyrosinase activities when the substrates were both L-tyrosine and L-DOPA, with inhibitions of 96.5 ± 0.2% and 87.9 ± 1.4%, respectively. As tyrosinase is an enzyme that plays a part in the metabolic process that generates hyperpigmentation of the human skin via the biosynthesis of melanin in the human skin, the compounds or formulations that possessed anti-tyrosinase activity were appealing for whitening effects.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, Mekvimol et al (2020) revealed that marigold flowers contain polyphenolic compounds of the flavonol group, namely laricitrin and its glycosides and have inhibitory benefits as an antibacterial against Streptococcus agalactiae. Romes et al (2021) found marigold flower extract contains natural photoantioxidants such as quercetin, gallic acid, and polyphenols having medicinal properties (antioxidative antityrosinase, antiviral, and antimicrobial). The extract protects the skin from UVA/UVB rays and improves skin and regenerative treatments (Mertha Adnyana and Sudaryati, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoid compounds and tannins work by damaging the cytoplasmic membrane and forming complexes with proteins through hydrophobic interactions, which ultimately disrupt the metabolism of bacterial cells resulting in lysis (Burlec et al, 2022;Zanovello et al, 2021;Zhang et al, 2020). Furthermore, previous research revealed that parts of the marigold flower have pharmacological benefits (Fu et al, 2019;Romes et al, 2021) and potential cosmetic raw materials (Kumar et al, 2021;Mekjaruskul et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The base formulation of face moisturizers consists in a solvent, emollients, humectants, emulsifiers, neutralizers, and thickening agents. Formulation stabilizers -such as chelating agents, antioxidants, and preservatives, and aesthetical attributes, for example fragrances, dyes, and pigments, can also be added to the formulation to make it more stable and attractive to consumers [28][29][30].…”
Section: Cosmetic Industrymentioning
confidence: 99%